PP.09.21: ENDOGENOUS OUABAIN AND ALDOSTERONE LEVELS. (June 2015) - Tentori, S.; Lanzani, C.; Messaggio, E.; Brioni, E.; Casamassima, N.; Simonini, M.; Hamlyn, J.M.; Manunta, P.
Abstract : Objective: Several studies indicate inappropriately elevated aldosterone (Aldo) secretion in ∼30% of newly discovered hypertensive patients. In primary aldosteronism homeostatic feedback loops between sodium balance and Aldo levels are disturbed and cardiovascular/renal damage is assumed to be secondary to high Aldo. However, other adrenocortical steroids including endogenous ouabain (EO) may be important. EO is elevated in sodium-loaded states, is a vasoconstrictor, raises blood pressure (BP), and promotes cardiovascular/renal damage. Design and method: Here, we investigated the relationship between circulating Aldo and EO and BP changes following an acute salt load in naïve hypertensive patients (NHP). Aldo cross-reactivity was < 1% in the EO assay. Results: NHP (488) were enrolled and grouped in tertiles by circulating Aldo (mean 1st 87 ± 2.18, 2nd 164 ± 1.83, and 3rd 332.3 ± 10.3 ng/dL). Baseline systolic and diastolic BPs were higher in the 3rd versus the 1st Aldo tertile (149.2 ± 1.17 vs 145.6 ± 1.11 and 98.4 ± 0.78 vs 92.5 ± 0.74 mmHg, p < 0.001, respectively). Circulating EO was higher in the 3rd Aldo tertile (285.7 ± 14.9 pmol/L) versus the 1st (239.0 ± 13.6 pM) and 2nd (211.4 ± 12.1 pM) tertiles (p < 0.01). Following an acute Na load, NHE in the 3rd Aldo tertile showed heightened salt–sensitivity of the pressure-natriuresis relationship (slope 0.013 ± 0.002 vs 0.004 μEq/mmHg/min, p = 0.008 after adjustment for sex, BMI, and age). In all subgroups circulating Aldo and PRA are suppressed after Na load. Plasma EO is not affected by Na load. Plasma K+ (4.07 ± 0.028 vs 3.93 ± 0.07 mEq/L) was higher (p = 0.002) in the 3rd Aldo tertile. Importantly, a direct (β = 0.116, p < 0.001) linear relationship was found between circulating Aldo and EO following adjustment for baseline BP, age, sex and BMI. β Conclusions: Among NHP, a large portion of patients have co-elevated circulating levels of EO and Aldo, and their BP is highly salt-sensitive. We suggest that EO and its target, the vascular myocyte α2 isoform of the Na-K ATPase, may contribute significantly to adverse cardiovascular and renal events in high aldosterone states.